The relation between birthweight, childhood body mass index, and overweight and obesity in late adolescence: a longitudinal cohort study from Norway, The Tromsø Study, Fit Futures - Evensen, Elin Kristin; Emaus, Nina; Kokkvoll, Ane Sofie; Wilsgaard, Tom; Furberg, Anne-Sofie; Skeie, Guri (BMJ Open, 2017)
Source at http://dx.doi.org/10.1136/bmjopen-2016-015576. Objectives : Childhood overweight/obesity is associated with later overweight/obesity. However, the association between birth weight and later overweight/obesity has not been established. The aim of this study was to investigate the relation between both birth weight and childhood body mass index (BMI), and adolescent overweight/obesity in a Norwegian population. Methods : The Tromsø Study – Fit Futures is a population-based cohort study conducted in 2010–2011 and 2012–2013 in Tromsø, Norway. A representative sample of 961 adolescents participated. Longitudinal anthropometric data were obtained from the Medical Birth Registry of Norway, childhood health records at 2–4 and 5–7 years of age, and repeated measurements at 15–18 and 18–20 years of age. Outcome was defined as normal weight (adult BMI <25 kg/m2) or overweight/ obese (adult BMI ≥2 5 kg/m2) at 15–20 years of age according to international age- and sex-specific cut-off values for children. Associations were investigated using generalised estimating equations. Results : In adjusted analyses, a 1-SD (586 g) higher birth weight was associated with a higher OR for overweight/obesity at 15–20 years of age (OR 1.25, 95% CI 1.06 to 1.48). Childhood BMI was also associated with overweight/obesity at 15–20 years of age: a 1-SD (1.35 kg/m2) increase in BMI at age 2–4 years rendered an OR of 1.66 (95% CI 1.40 to 1.96); a 1-SD (1.83 kg/ m2) increase in BMI at age 5–7 years rendered an OR of 3.23 (95% CI 2.56 to 4.07). When compared with normal-weight children, those with severe overweight/ obesity in childhood (adult BMI ≥27 kg/m2) showed stronger associations with overweight/obesity at 15–20 years of age: OR 3.01 (95% CI 1.47 to 6.18) and OR 11.51 (95% CI 6.63 to 19.99) at ages 2–4 and 5–7, respectively. Conclusion : Associations between birth weight and overweight/obesity at 15–20 years of age were modest, whereas the influence of BMI at 2–4 and 5–7 years on overweight/obesity at 15–20 years was moderate ...